Modern Challenges of Adjusting the Effectiveness of the Application of Laws (on the Example of Tax and Legal Regulation) - Lohvinova, Olha (Problems of legality, 2024)
The relevance of the research topic is determined by the current state of social relations. It is noted that the analysis of modern social relations cannot be carried out outside the boundaries of significant challenges that require not only their understanding, but also consideration in the relevant reform measures. The most important challenges today are the following: Russia's war with Ukraine; European integration processes that characterize modern trends in Ukrainian development; digitization of all aspects of public life. Given the problems associated with this, the article defines both objective reasons that affect tax relations, as well as requirements that are subjective in nature. The purpose of the article is to highlight problematic aspects of the state of modern legal regulation. Attention is focused on the fact that war, European integration and digitalization are among the most influential factors in this aspect. It is clear that they cannot fail to influence the traditional legal means that guarantee the effectiveness of tax legislation. These aspects are the subject of analysis. Traditional methods of scientific knowledge are used in the research, thanks to which a systematic idea is formed about the reasons for adjusting legal means of influence on tax relations. The characteristics of the influence of martial law on tax regulation are carried out depending on the stages. The beginning of the first is associated with 2014, while the second - with 2022. Despite common features (narrowing of the territories where Ukrainian jurisdiction exists, reduction of the tax base and tax-paying taxpayers, etc.), differences in the content of these stages have been singled out. European integration processes, which reflect the movement of Ukraine towards the European community, provide for the adjustment of the nature and content of tax legislation in the following directions: a) adaptation of the current tax legislation of Ukraine to European requirements; b) consideration of European prescriptions at the stage of development of zocono projects; c) achieving a balance of acts of the national legislation system. Three areas of relations, which most fundamentally affect the legal status of tax regulation, have been studied. The prospects of tax changes depending on the state of war, the prospects of the impact of harmonization of EU legislation and national legislation, the need to take into account the processes of digitalization of tax relations are considered. On the basis of the conducted research, conclusions were made and recommendations were made regarding the harmonization of the prescriptions of both exclusively tax norms and tax norms on the border with other industry regulations. Adjustment of the current set of legislative norms determines the importance of a systematic approach to the turnover of virtual assets. The formation of a generalized, systematic approach to these relations is fundamentally important. In order to achieve such a state, it is very important to supplement the private law means of regulating the circulation of virtual assets with effective tools of public and legal influence (taxation, supervision, public control). The study analyzes the substantive factors of the regulation of such relations proposed by the two draft laws.